Paródia e Auto-Reflexividade no Filme Romance, de Guel Arraes. - Barbosa, Afonso Manoel da Silva (2013)
This dissertation aims to analyse the film Romance by Guel Arraes. The study aims to discuss the filmic text from central axis such as meta-fiction and the investment in a parodic proposal which works laughter at a level more critical and ironic when compared to other cinematographic works from the director. The research aims to observe the connection between the ludic and the critical (PUCCI, 2007) in traces of a postmodern affiliation (HUTCHEON, 1991). The process involving the artistic conceptions of Guel Arraes (FIGUEIRÔA; FECHINE, 2008) is one of the aspects that we propose to point out, relating the work with other works from the director, mainly, Lisbela e o prisioneiro and O Auto da Compadecida, as well as data from Jorge Furtado s artistic production, co-writer of Romance, like the feature film Saneamento Básico. Furthermore, the study aims to highlight the elements that substantiate the dialogical processes (STAM, 2000) between the various languages that compose the work, investigating, for example the relationship established with other texts, such as Tristão e Isolda. The dissertation also intend to observe the resources from the northeastern culture used in the adaptation of the medieval history, which also have similarities with other literary works (BÉDIER, 2012); (SUASSUNA, 2012). The dissertation still aims to bring up for discussion the conflict established around the creative process in the context of audiovisual production represented diegetically, with attention to categories such as character and plot.